Report of Case Study (ENT300) Potterhead Malaysia / Muhammad Syazwi Mohd Yusri...[et al.] - Mohd Yusri, Muhammad Syazwi; Moestaffa, Muhammad Shazrul Hafizam; Abdul Razak, Muhammad Aiman Hakimi; Ahmad Shabri, Nurul Izzati; Ahmad Tajuddin, Nurul Huda; Husain, Siti Salwa (2020)
pandemic outbreak lately. It does not stop us from continuing our task to finish the assignment. We are truly grateful for the fulfilment of this case study assessment which is required to be accomplish as a first course work for the fundamentals of entrepreneurship course. Special appreciation to family and friends for supporting us to work on this assessment. This case study has been prepared with the cooperation and encouragement from many people. A assive gratitude also would be given to our lecturer Sir Mohd Najmie Osman and his thoughtfulness in guiding us toward the process of completion of this case study. He had assisted us by providing a lot of useful information. The absence of him would cause us enormous difficulty in finishing the assignment given. We successfully able to face the problems appear during doing our research. We have been wiser in dealing with obstacles. The interview session for the case study had feed us organizing, marketing, operational process, financial planning and training plan and any other information needed for a new entrepreneur to start a business. Let us not forget to give our deepest thanks to Madam Mardilyn King Phaik wang, the founder of Potterhead Malaysia who willing to accept our invitation to conduct an interview session even though we did it through online video conference using the application Zoom. She shared her business knowledge with us. She also has been enthusiastic on helping us to do our best in finishing this project. Lastly, we are all optimistic on the case study in given us comprehension in entrepreneurship world and element on becoming an ideal entrepreneur in future.